Electrical, electrochemical and structural studies of a chlorine-derived ionic liquid-based polymer gel electrolyte - Gupta, Ashish; Jain, Amrita; Kumari, Manju; Tripathi, Santosh K. (Beilstein Journal of Nanotechnology, 2021)
In the present article, an ionic liquid-based polymer gel electrolyte was synthesized by using poly(vinylidene fluoride-co-hexafluoropropylene) (PVdF-HFP) as a host polymer. The electrolyte films were synthesized by using the solution casting technique. The as-prepared films were free-standing and transparent with good dimensional stability. Optimized electrolyte films exhibit a maximum room-temperature ionic conductivity of σ = 8.9 × 10−3 S·cm−1. The temperature dependence of the prepared polymer gel electrolytes follows the thermally activated behavior of the Vogel–Tammann–Fulcher equation. The total ionic transference number was ≈0.91 with a wider electrochemical potential window of 4.0 V for the prepared electrolyte film which contains 30 wt % of the ionic liquid. The optimized films have good potential to be used as electrolyte materials for energy storage applications.
Keywords: ionic liquid; polymer gel electrolytes; solution casting technique; transference number